Redesain Pondok Pesantren di Aceh Singkil Dengan Pendekatan Kontekstual - Syafira Wahyuni Anasti T; Faiza Aidina (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Pesantren Darul Muta’allimin is the oldest Islamic boarding school in Aceh Singkil and is currently facing various challenges in its daily operations. These challenges include limited capacity, functional transformation of buildings, physical degradation and the use of less sustainable materials, as well as spatial arrangements that are not responsive to the functional needs of the pesantren. Such conditions affect not only the effectiveness of the educational activities but also the comfort and spatial experience of its users.